2008
DOI: 10.1016/j.tig.2008.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Whole chromosome instability and cancer: a complex relationship

Abstract: Although chromosome mis-segregation is a hallmark of cancer cells, its genetic basis and role in malignant transformation remain poorly understood. In recent years, several mouse models have been generated that harbor gene defects that perturb high-fidelity chromosome segregation. Analysis of these models has revealed that whole chromosome instability (W-CIN) can cause, inhibit or have no effect on tumorigenesis. Here we propose that the effect of W-CIN on tumor development depends on the particular W-CIN gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
147
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(150 citation statements)
references
References 75 publications
(104 reference statements)
2
147
0
1
Order By: Relevance
“…63,64 When 'low-grade' (i.e., survivable) missegregation results in the loss of a gene that promotes faithful chromosome segregation and maintenance (or gain of another copy of a gene that disturbs these processes), then the cell acquires CIN -essentially, the ability to shuffle its genome until a stable, malignant phenotype is procured. 131 By contrast, in the absence of clustering, supernumerary centrosomes result in spindle multipolarity, which may cause aneuploidy of a mortally high grade. Alternatively, multipolar cells may arrest in mitosis and succumb to death via other mechanisms, 63,122 as depicted in Figure 4c.…”
Section: Disperse and Destroy: Induction Of Spindle Multipolarity As mentioning
confidence: 99%
“…63,64 When 'low-grade' (i.e., survivable) missegregation results in the loss of a gene that promotes faithful chromosome segregation and maintenance (or gain of another copy of a gene that disturbs these processes), then the cell acquires CIN -essentially, the ability to shuffle its genome until a stable, malignant phenotype is procured. 131 By contrast, in the absence of clustering, supernumerary centrosomes result in spindle multipolarity, which may cause aneuploidy of a mortally high grade. Alternatively, multipolar cells may arrest in mitosis and succumb to death via other mechanisms, 63,122 as depicted in Figure 4c.…”
Section: Disperse and Destroy: Induction Of Spindle Multipolarity As mentioning
confidence: 99%
“…To investigate the effects of genomic instability and resulting aneuploidy on carcinogenesis, various mouse models have been developed, mainly by targeting mitotic or other cell cycle regulators (Foijer, Draviam, & Sorger, 2008; Rao, Yamada, Yao, & Dai, 2009; Ricke, van Ree, & van Deursen, 2008; Schvartzman, Sotillo, & Benezra, 2010). Shugoshin‐1 (Sgo1) protects cohesin proteins and centrosome integrity (Salic, Waters, & Mitchison, 2004; Schöckel, Möckel, Mayer, Boos, & Stemmann, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Polyploidy is often observed in cancer cells, but it is not clear whether this phenomenon is a cause or result of cancer development (26,30,31). Previous studies showed that the failure of cytokinesis results in cell polyploidy and subsequent cell death (32) and that freshly generated polyploid cells are prone to undergo Bax-dependent mitochondrial membrane permeabilization and subsequent apoptosis (33).…”
Section: Discussionmentioning
confidence: 99%